Faktor-Faktor Yang Mempengaruhi Keluhan Saluran Pernapasan Pada Pekerja di PT. X Plant Parung Bogor - Novita Amalia; Cornelis Novianus (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
The construction industry produces air pollutants in the work environment in the form of dust, such as PM2.5. PM2.5 dust exposures have an impact on the risk of occupational diseases, so that workers become unproductive. The purpose of this study is to determine the relationship between PM2.5 concentration in the work environment and the presence of respiratory complaints in industrial workers in the production section at PT. X Plant Parung, Bogor. The design of this study was cross sectional. This study will be do in 2019. Workers sample use the total sampling method. The population was 69 workers. The sample of PM2.5 concentration collect by using MiniVol Tartical Portable Air Sampler. As for the variables of respiratory complaints, age, years of service, history of respiratory diseases, smoking status, and the use of masks were conducted by interview using a questionnaire instrument. The analysis used was univariate and bivariate using the chi square test. Univariate results showed respiratory complaints (72.5%), PM2.5 concentrations at location point 1 (39.1%), location point 2 (33.3%), location point (27.6%), age (63.8) %), years of service (62.3%), history of respiratory illness (68.1%), smoking status (75.4%), and mask use (58%). Bivariate results indicate variables related to respiratory complaints, namely age, years of service, smoking status and the use of masks.